Anaerobic Respiration on Self‐Doped Conjugated Polyelectrolytes: Impact of Chemical Structure. (26th April 2017) - Kirchhofer, Nathan D.; McCuskey, Samantha R.; Mai, Cheng‐Kang; Bazan, Guillermo C.
Abstract: We probe anaerobic respiration of bacteria in the presence of conjugated polyelectrolytes (CPEs). Three different CPEs were used to probe how structural variations impact biocurrent generation from Shewanella oneidensis MR‐1. For the self‐doped anionic CPE only, absorption spectroscopy shows that the addition of S. oneidensis MR‐1 leads to the disappearance of the polaron (radical cation) band at >900 nm and an increase in the band at 735 nm due to the neutral species, consistent with electron transfer from microbe to polymer. Microbial three‐electrode electrochemical cells (M3Cs) show an increase in the current generated by S. oneidensis MR‐1 with addition of the self‐doped CPE relative to other CPEs and controls. These experiments combined with in situ cyclic voltammetry suggest that the doped CPE facilitates electron transport to electrodes and reveal structure–function relationships relevant to developing materials for biotic/abiotic interfaces.